PARTISIPASI MASYARAKAT DALAM PROGRAM VAKSINASI COVID-19 DI DESA WANARAJA KECAMATAN WANARAJA KABUPATEN GARUT - Yagus Triana H.S; Novi Agustina; Liestia Dewi Nuraisyah (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The Indonesian government has issued Presidential Decree Number 14 of 2021 concerning the procurement of COVID-19 vaccines as part of its efforts to reduce the infectivity and spread of COVID-19. Wanaraja Village is among the villages where the government provides free vaccinations. Despite the vaccination campaign, there is still resistance among many people who are unwilling to be vaccinated.The aim of this study was to assess community participation in the COVID-19 vaccination program in Wanaraja Village, Wanaraja District, Garut Regency. The research method used for this study is descriptive qualitative analysis, involving data collection through interviews, observations, and discussions.The evaluation of community participation in the COVID-19 vaccination program is based on Cohen and Uphoff's theory, which comprises indicators such as participation in implementation, utilization, and evaluation. The findings reveal that public participation in the COVID-19 vaccination remains low due to the perception among some individuals that the virus is a government propaganda or conspiracy, concerns about the safety of vaccine ingredients, and the circulation of misinformation and hoaxes in the community.